Hyperexpression of TNF-Stimulated 6 (TSG-6) of HumanTracheal Aspirate and Bronchial Alveolar Lavage from Heavy-Smoker and Lung TB - Trihadi, Djoko (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: TSG-6, an inflamation-associated protein, forms covalent complexes with heavy-chains from TNF. These protein potentiating the antiplasmin activity of this serine protease inhibitor. The aim of study was to determine and show that TSG-6 are present in Bronchoalveolar Lavage (BAL) from patients with lung TB and heavy smoker.Design and Methods: Experiments conducted in vitro with purified components revealed that TSG-6 had immunodetection in the Human Tracheal Aspirates (HTA) and BAL of heavy smoker and Lung Tuberculosis.Results: Immunoprecipitation revealed that TSG-6 accounts in airways hyperresponsiveness for significant proportion of BAL and HTA, but not in control (p < 0,01). TSG-6 relevant protease inhibitor in airway secretion. In primary cultures of differentiated human airway epithelial, which suggest that TSG-6 may be induced by TNF. Our results suggest that TSG-6 may play an important protective role in bronchial epithellium buy increasing the antiprotese screen on the airway lumen. The present study identifies a novel function of TSG-6 by a distinct mechanism system regulated, enhancement of anti TK activity, and provides a rational for this activity within the context of inflamed airways. These findings correlate with the observed increases in protein expressions in human HTA and BAL.Conclusions: TSG-6 are hyper-expressed in airway epithelial cells in cultures of smoker and lung TB. The interactions of TSG-6 with other molecules are also potentially important to the pathophysiologic aspects of inflammatory airways diseases that remain to be elucidated (Sains Medika, 3(1):31-40).